2008
DOI: 10.1016/j.foodhyd.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between bacterial surfaces and milk proteins, impact on food emulsions stability

Abstract: Bacteria possess physicochemical surface properties such as hydrophobicity, Lewis acid/base and charge which are involved in physicochemical interactions between cells and interfaces. Moreover, food matrices are complex and heterogeneous media, with a microstructure depending on interactions between the components in media (van der Waals, electrostatic or structural forces, etc.). Despite the presence of bacteria in fermented products, few works have investigated how bacteria interact with other food component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 38 publications
1
46
0
3
Order By: Relevance
“…Several macromolecules are located on the bacterial surfaces which enable bacteria to interact specifically or non-specifically with other compounds through electrostatic, hydrophobic interactions. Addition of bacteria to oil/water emulsions stabilized by milk proteins (sodium caseinate, whey protein concentrate or whey protein isolate) at different pH (from 3 to 7.5) affected the emulsions' stability depending on the surface properties of strains and also on the characteristics of emulsions (Ly et al 2008). The surface charge and hydrophobicity of the bacteria were suggested to be involved in its interaction with proteins (Ly et al 2008).…”
Section: Interaction Between Probiotics and Capsular Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several macromolecules are located on the bacterial surfaces which enable bacteria to interact specifically or non-specifically with other compounds through electrostatic, hydrophobic interactions. Addition of bacteria to oil/water emulsions stabilized by milk proteins (sodium caseinate, whey protein concentrate or whey protein isolate) at different pH (from 3 to 7.5) affected the emulsions' stability depending on the surface properties of strains and also on the characteristics of emulsions (Ly et al 2008). The surface charge and hydrophobicity of the bacteria were suggested to be involved in its interaction with proteins (Ly et al 2008).…”
Section: Interaction Between Probiotics and Capsular Materialsmentioning
confidence: 99%
“…Addition of bacteria to oil/water emulsions stabilized by milk proteins (sodium caseinate, whey protein concentrate or whey protein isolate) at different pH (from 3 to 7.5) affected the emulsions' stability depending on the surface properties of strains and also on the characteristics of emulsions (Ly et al 2008). The surface charge and hydrophobicity of the bacteria were suggested to be involved in its interaction with proteins (Ly et al 2008). A study revealed that the interaction of probiotics with milk proteins is strain specific and that the type of milk protein and pH affect these interactions being non-specific in case of casein and specific in case of whey proteins (Burgain et al 2013b).…”
Section: Interaction Between Probiotics and Capsular Materialsmentioning
confidence: 99%
“…The surface hydrophobicity of yeast cells with or without treatment of nanoemulsion was evaluated by MATH assay (Ly et al 2008). In this experiment, 1.5 ml of freshly grown S. cerevisiae cells that contain approximately 1 9 10 7 CFU/ml cells in PDB medium was collected by centrifugation and then resuspended in 1 ml of orange oil nanoemulsion or PBS (pH 7.4).…”
Section: Microbial Adhesion To Hydrocarbon (Math) Assaymentioning
confidence: 99%
“…For emulsion systems, oil droplets can be kinetically stabilized in the continuous aqueous phase by adopting appropriate emulsifiers and engineered interfaces. Milk proteins are among the best natural surfactants for food applications (29). Interfacial properties of milk proteins, particularly whey proteins, can be improved by conjugation with more hydrophilic oligosaccharides and polysaccharides (25).…”
mentioning
confidence: 99%